Rosacea as a General Medical Problem: Pathogenesis, Clinical Picture, Principles of Management - Sukhanov, Dmitriy S.; Alexeeva, Yulia S.; Timofeev, Eugene V. (Juvenis Scientia)
Rosacea is a chronic inflammatory dermatosis characterized by facial skin lesions such as erythema, papules, pustules, phymas, and ocular involvement. In Russia, rosacea affects 5% of the population, while in European countries it ranges from 1.5% to 10%. This review presents the pathogenesis, classification, and modern approaches to the treatment of rosacea in Russia. Although rosacea is typically managed by specialists, it is also of interest to general practitioners. The goals of rosacea treatment are to reduce symptom severity and prevent disease exacerbations, thereby extending periods of stable remission. Despite advances in understanding the molecular mechanisms of the disease, development of classification approaches, and phenotype-specific therapy, treatment failures and severe cases of rosacea persist. In addition to timely diagnosis and differential diagnosis in therapeutic practice, it is necessary to consider the increased risk of associations between rosacea and internal organ pathologies, as well as potential drug interactions among various medications used to treat this disease.